Morphometric Analysis of Adult Acromion Process of Scapula in South Indian Population - Begum, Masooma; B H Shiny Vinila; Asra Anjum (Academia Anatomica International, 2021)
Background: Morphometric analysis of the acromion process is important in shoulder joint pathologies and the structures passing through the subacromion space or structures present underneath the coracoacromial arch are more prone to undergo impingement and end with impingement syndrome of the shoulder joint. Knowledge on the morphometry of the acromion process is essential before planning surgical treatment of the impingement syndrome such as, acromioplasty or acromionectomy. The present study is aimed to focus on the morphometric analysis of the acromion process. Subjects and Methods: The present study was carried on 100 dry adult scapulae in which 50 were right and 50 were left. The following parameters were measured; length of the acromion, width of the acromion, coracoacromial distance and the acromioglenoidal distance. All the parameters were measured using vernier caliper. Results: The mean length of the acromion process was 42.55mm and 41.43mm on the right and the left sides respectively. The mean width of the acromion process was 23.12mm and 22.8mm on the right and the left sides respectively. The mean coracoacromial distance was 34.16mm and 34.15mm on the right and the left sides respectively. The average acromioglenoid distance was 24.48mm and 24.52mm on the right and the left sides respectively. Conclusion: The morphometric data of this study will be of great importance for the orthopaedic surgeon while treating the impingement syndrome and other surgeries of shoulder joint.